EFFECT OF DIETARY SUPPLEMENTATION OF FENNEL SEEDS (FOENICULUM VULGARE) ON IMPROVING EGG QUALITY IN LAYING HENS - M. Haglan; A. Majed (مجلة الأنبار للعلوم الزراعية, 2022)
The purpose of the study was to examine the impact of adding Fennel seeds (Foeniculum vulgare L.) into the diets of laying hens on egg quality. This study was conducted in poultry fields belonging to Department of Animal Production, College of Agriculture, and University of Anbar for 12 weeks.  A total of 72 laying hens (Lohman Brown) were used in this experiment, at age 43 weeks. Hens were randomly distributed to six treatments groups and with four replicates per treatment (3 hens/replicate). The treatments were T1: (positive control) based diet containing 1% hydrogenated vegetable fat, T2: (negative control) based diet containing 1% Sheep fat, T3, T4, T5 and T6 The based diet contained 1% Sheep fat + supplementation of 0.25, 0.50, 0.75 and 1% Fennel seeds powder sequentially.  The results showed significant (P≤0.05) differences for the supplementation treatments on the qualitative characteristics of egg quality, as treatment T6 was significantly (P≤0.05) superior to the rest of the experimental treatments in shell weight, yolk weight, yolk index, percentage of Albumen weight %, Albumen weight (g) and Haugh Unit. Treatments T5 and T6 were significantly (P≤0.05) superior to the rest of the experimental treatments in shell thickness, percentage of yolk weight%, and Albumen index, while there was no significant effect (P≤0.05) of the supplementation treatments on (percentage of shell weight%) compared to the two control treatments T1 and T2. It was concluded adding 0.75 and 1% Fennel seeds powder to laying hens' diets improved quality of eggshell, yolk, and egg white.